Community Service to Educate The Development of Green Open Space in Kelurahan Purbayan, Kemantren Kotagede - Kurniati, Ayu Candra (ReTII, 2022)
The existing area of public green open space in the city of Yogyakarta in 2020 is 220.45 ha, or 6.64% of the total area of the city of Yogyakarta. Meanwhile, Kemantren Kotagede has an area of 307 ha, with a composition of 35.94 ha of public green open space and 18.21 ha of private green open space, sum up the total green open space area in the Kemantren Kotagede is 54.15 ha. The lack of availability of green open space in Kemantren Kotagede, especially in Purbayan Village, requires education regarding the importance of green open space and some recommendations for providing green open space in the settlement area of Kelurahan Purbayan Kemantren Kotagede. The problem in Purbayan Village is the lack of information and knowledge about the importance of providing green open space and how to develop green open space in residential areas. The method of implementation is to provide education related to understanding the importance of green open space and conduct focus group discussions to explore and make agreement on issues, recommendations and the community`s participation of the Kelurahan Purbayan to provide and develop green open space. The results showed that the need for a green community could be met by utilizing the PKK organization, using vertical gardens and tabulampot for limited land, and mapping the potential of public green open space. This community service activity is important to provide information and explore the community's own ideas to overcome issues related to the provision and development of green open space in accordance with the characteristics of Purbayan Village.